2012
DOI: 10.1590/s0365-05962012000200008
|View full text |Cite
|
Sign up to set email alerts
|

Repair of cutaneous wounds with the use of low cost surgical glue

Abstract: BACKGROUND: The advantages of the cyanoacrylates in cutaneous synthesis have been often demonstrated in the literature. However, these products have been underutilized in Brazil due to the high costs of the 2-octil-cyanoacrylate. Besides, few studies have been done with the more economically accessible form, the 2-etil-cyanoacrylate, as a cutaneous tissue adhesive. OBJECTIVE: To evaluate the effectiveness of the closing of cutaneous lesions using ECA. METHOD: This was a prospective study in which 46 wounds wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 13 publications
0
4
0
Order By: Relevance
“…Previous studies have shown that stapling is 5-7 times quicker than suturing [1]; [10]; [11]. Souza et al demonstrated that tissue adhesives were 3 times quicker than suture [12]. In contrast, Coulthard et al reported that suture was quicker than tissue adhesive [12].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Previous studies have shown that stapling is 5-7 times quicker than suturing [1]; [10]; [11]. Souza et al demonstrated that tissue adhesives were 3 times quicker than suture [12]. In contrast, Coulthard et al reported that suture was quicker than tissue adhesive [12].…”
Section: Discussionmentioning
confidence: 99%
“…Souza et al demonstrated that tissue adhesives were 3 times quicker than suture [12]. In contrast, Coulthard et al reported that suture was quicker than tissue adhesive [12]. Comparison of the time to treatment in different modalities demonstrated that Group 2 and 3 were significantly quicker compared to Group 1, a condition which was due to absence of need for local anesthesia and ease of application with staplers or tissue adhesives.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations